PENGETAHUAN, SIKAP, DAN PERILAKU BERAGAMA PESERTA DIDIK DI MADRASAH IBTIDAIYAH DAN SEKOLAH DASAR DI KOTA MAKASSAR - Umar Sulaiman; Mihrani; Eka Damayanti (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2021)
This study aims to find differences in knowledge, attitudes, and religious behavior of the students at Madrasah Ibtidaiyah and Public Elementary Schools in Makassar. This study was a comparative quantitative on the population of all sixth-grade students. There were 69 students of MI Al Abrar Makassar and 96 students of SD Inpres Unggulan BTN Pemda Makassar. The sampling technique used was random sampling techniques by considering homogeneity. The instruments used in data collection were tests, attitude scales, and questionnaires. The data were analyzed using descriptive and inferential statistics (independent sample t-test). The results showed: (1) There are differences in religious knowledge between students of MI Al-Abrar Makassar and SD Inpres Unggulan BTN Pemda Makassar (t-count value of 4.599> t-table = 1.99547); (2) There is no difference in religious attitudes between students of MI Al-Abrar Makassar and SD Inpres Unggulan BTN Pemda Makassar (t-count = 1.231 < t-table = 1.99547); (3) There are differences in religious behavior between students of MI Al-Abrar Makassar and SD Inpres Unggulan BTN Pemda Makassar (t-count = 2.220> t-table = 1.99547). The results of the study can be considered in making policies for education, teachers, and religious teaching teams to put students' religious attitudes positively.